PENGARUH KOMIK DIGITAL BERBASIS KEARIFAN LOKAL MELAYU TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V SEKOLAH DASAR - Mia Ningsih; Waliyul Maulana Siregar; Nurmayani Nurmayani; Apiek Gandamana; Laurensia Masri Perangin Angin (Universitas Negeri Medan, 2026)
This study aims to determine the effect of using digital comics based on Malay local wisdom on Pancasila Education learning outcomes for fifth-grade students at SDN 101744, Klambir Village. This study used a quantitative approach with a quasi-experimental nonequivalent control group design. The sample consisted of two classes: Class VA as the control class using the lecture or conventional method, and Class VB as the experimental class receiving treatment. Data were collected through pretests and posttests and analyzed using an independent sample t-test. The results showed a significant effect between the implementation of digital comics based on Malay local wisdom and the implementation of digital comics based on Malay local wisdom. Students learning using this method, or the experimental class, experienced a significant increase in learning outcomes, at 81.48%, compared to 32% in the control class. Data analysis revealed a t-test value greater than the t-table (6.102>2.010), with a significant value (2-tailed) of less than 0.05 (0.000<0.05). The hypothesis test results indicate that the H0 is rejected and the H is accepted. Therefore, the application of digital comic media based on Malay local wisdom to improve student learning outcomes in Pancasila Education has proven effective.